Automated electrophilic radiosynthesis of [18F]FBPA using a modified nucleophilic GE TRACERlab FXFDG. (October 2015) - Mairinger, Severin; Stanek, Johann; Wanek, Thomas; Langer, Oliver; Kuntner, Claudia
Abstract: We modified a commercially available synthesis module for nucleophilic [ 18 F]fluorinations (TRACERlab TM FXFDG, GE Healthcare) to enable the reliable synthesis of 2-[ 18 F]fluoro-4-borono-l -phenylalanine ([ 18 F]FBPA) via direct electrophilic substitution of 4-borono-l -phenylalanine with [ 18 F]F2 gas. [ 18 F]FBPA was obtained with a RCY of 8.5±2.0% and a radiochemical purity of 98±1% in a total synthesis time of 72±7 min ( n =22). The modified synthesis module might also be useful for the synthesis of other [ 18 F]radiopharmaceuticals via electrophilic substitution reactions while still being suitable for nucleophilic substitution reactions. Graphical abstract: Highlights: Automated synthesis of [ 18 F]FBPA was developed via reaction of BPA with [ 18 F]F2 . [ 18 F]FBPA was obtained with a RCY of 8.5±2.0%. Nucleophilic synthesis module was adapted for electrophilic [ 18 F]fluorinations. Modified synthesis module may also enable other electrophilic [ 18 F]fluorinations.